River Morphological Study of Downstream Paneki River in Palu Watershed Following The Earthquake and Liquefaction Disaster at Central Sulawesi - James A Kaunang; Dhemi Harlan; Aries S Moerwanto; Radia Zulfikar (Jurnal Teknik Sipil, 2023)
Abstract An earthquake that struck Central Sulawesi Province in 2018 triggered liquefaction in several locations such as Jono Oge village where the middle stream of Paneki River flows. Liquefaction caused the Paneki River wash in the densely populated settlement became narrower and shallower due to “flowing” material. In response, the Ministry of Public Works and Housing initiates River Improvement and Sediment Control in Paneki River project. The implementation of this project will affect the river’s behaviour, especially its morphological aspects. Therefore, a study of the discharge capacity and morphological analysis due to said project is needed. The study is conducted using numerical model simulation to obtain the river discharge capacity and river morphological changes in form of bed changes. The model simulation result shows the maximum discharge capacity of Paneki river is 259.81m3/s, also the bed upstream and downstream of the river degrade, with consolidation dam - 1 (CD-1) stabilized the river bed upstream of the dam to 2740 m relative to the river outlet. Stabilization due to the position of CD - 2 could be described using the following equation of y = -1018 ln(x) + 7208.1, the average degradation of the downstream area could be described with y= 0.017x0.6701. Keywords: River morphology, numerical model, bed degradation. Abstrak. Gempa bumi yang melanda Provinsi Sulawesi Tengah pada tahun 2018 memicu terjadinya likuifaksi di beberapa lokasi seperti Desa Jono Oge tempat Sungai Paneki mengalir. Likuifaksi menyebabkan aliran sungai di desa tersebut menjadi sempit dan dangkal akibat material yang “mengalir”. Kementerian Pekerjaan Umum dan Perumahan Rakyat melakukan pekerjaan Perbaikan Sungai dan Pengendalian Sedimen di Sungai Paneki untuk mengatasi dampak liquifaksi, dimana pelaksanaan pekerjaan ini akan mempengaruhi perilaku sungai, terutama morfologinya. Oleh karena itu, studi tentang kapasitas debit dan analisis morfologi sungai karena proyek tersebut perlu diperlukan. Penelitian ini dilakukan dengan menggunakan model numerik untuk mengetahui perubahan morfologi sungai berupa perubahan dasar dan kapasitas debit sungai. Hasil simulasi menunjukkan kapasitas debit maksimum adalah 259,81m3/s, dasar sungai di hulu dan hilir sungai mengalami penurunan, dengan bendungan konsolidasi - 1 (CD-1) menstabilkan dasar sungai di hulu bendung hingga 2740 m relatif dari outlet sungai. Stabilisasi akibat posisi CD - 2 dapat digambarkan dengan persamaan: y = -1018 ln(x) + 7208.1, degradasi rata-rata daerah hilir dapat digambarkan dengan y= 0.017x0.6701. Kata-kata Kunci: Morfologi sungai, model numerik, degradasi dasar sungai.